Global Trends and Prospects for Post-Pandemic International Tourism Development in Uzbekistan - Mamarizoyev Jahongir Isoxonovich; Turaeva Suriya Telmanovna (Universitas Muhammadiyah Sidoarjo, 2025)
Background: International tourism has undergone profound changes due to the COVID-19 pandemic, significantly affecting global and regional travel flows. Specific Background: Uzbekistan, with its rich cultural heritage and strategic location, has seen evolving patterns in tourism development, especially in the post-pandemic context. Knowledge Gap: Despite the global attention to tourism recovery, limited studies have focused on Uzbekistan's unique trajectory and adaptive strategies in this period. Aims: This study aims to analyze the trends and prospects of international tourism in Uzbekistan from 2012 to 2023, with an emphasis on post-pandemic structural transformations. Results: The findings reveal that digitalization, sustainable practices, and personalized travel have become central to the sector's revival. Key enablers of growth include visa liberalization, infrastructure modernization, and innovative heritage management. Novelty: By integrating comparative global data with national statistics, this research provides a nuanced understanding of Uzbekistan’s tourism resilience and strategic adaptation. Implications: The study offers policy-relevant insights for enhancing the competitiveness of Uzbekistan’s tourism industry, highlighting the importance of aligning national strategies with global best practices amid ongoing uncertainties. Highlights: Post-pandemic recovery strategies shaped tourism’s transformation. Infrastructure and visa reforms boost international arrivals. Innovation and sustainability drive long-term tourism growth. Keywords: International Tourism, Post-Pandemic Recovery, Sustainable Development, Digitalization